2017
DOI: 10.1016/j.apmr.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Very High Prevalence of Frozen Shoulder in Patients With Type 1 Diabetes of ≥45 Years' Duration: The Dialong Shoulder Study

Abstract: The point prevalence of frozen shoulder in patients with long-lasting type 1 diabetes was 59%, and the lifetime prevalence was 76%. The diabetes group had more shoulder disability than diabetes-free subjects. The historical HbA level was associated with increased shoulder disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 99 publications
6
34
1
2
Order By: Relevance
“…In patients with T1D in Sardinia, adhesive capsulitis was diagnosed in 35.1%. In another study of T1D with a long duration (>45 years), 59% of the patients had frozen shoulder 92 . The prevalence of adhesive capsulitis in the large T1D cohort described in Larkin et al was 31%.…”
Section: Prevalence Of Self-reported Ueismentioning
confidence: 95%
“…In patients with T1D in Sardinia, adhesive capsulitis was diagnosed in 35.1%. In another study of T1D with a long duration (>45 years), 59% of the patients had frozen shoulder 92 . The prevalence of adhesive capsulitis in the large T1D cohort described in Larkin et al was 31%.…”
Section: Prevalence Of Self-reported Ueismentioning
confidence: 95%
“…The association between diabetes and AC was first recognized by Bridgman (1972) who found that 10.8% of diabetic patients had AC as compared to 2.3% for nondiabetic patients [8]. Subsequent studies have supported this association and reported a prevalence of 10-76% in type 1 and 7-30% in type 2 diabetes as compared to 0-10% in the general population [9][10][11][12]. Adhesive capsulitis was also reported to be associated with age in both types of diabetes and with the duration in type 1 diabetes [9][10][11]13].…”
Section: Introductionmentioning
confidence: 97%
“…Subsequent studies have supported this association and reported a prevalence of 10-76% in type 1 and 7-30% in type 2 diabetes as compared to 0-10% in the general population [9][10][11][12]. Adhesive capsulitis was also reported to be associated with age in both types of diabetes and with the duration in type 1 diabetes [9][10][11]13]. The pathophysiology that predisposes diabetics for the development of AC is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of latter are frozen shoulder (FS) and hemiplegic shoulder pain (HSP). While the prevalence of FS among the general population is 2%–4%, it affects up to 59% of patients with long‐term diabetes mellitus . HSP is a frequent unfortunate stroke sequel with the reported incidence of shoulder pain of 47% at 12 months .…”
Section: Introductionmentioning
confidence: 99%